Construction Technology Diffusion in Developing Countries: Limitations of Prevailing Innovation Systems - Ligny, Emilia van Egmond deWilde de; Erkelens, Peter (Penerbit Universiti Sains Malaysia, 2008)
The diffusion of innovative technologies in the market is usually a complex and difficult process with a varying degree of success and the effects of the diffused innovative technologies are very un-balanced. The objective of our research is to gain insight into the reasons why the diffusion of innovative technology fails, even though they promise a superior performance compared to incumbent technologies. Drawing on innovation systems theories, we have identified and used the concepts of technological regime, actor network and technology sets to analyze technology diffusion in a case study in the dwelling construction industry in Costa Rica. The results showed bottlenecks in the prevailing innovation system that curtailed the diffusion of an innovative construction technology.